2020
DOI: 10.1039/d0ra00335b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bitumen and a novel multiple synergistic method for reducing bitumen viscosity with nanoparticles and surfactants

Abstract: This paper is concerned with the formation of bitumen during the drilling of the H oilfield in Iraq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 45 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…The location of the study area is in the L block in the eastern Ordos Basin (Figure 1). It is in the intersection part of the Jinxi Flexural Zone and the Yishan Slope 1,27 . The Upper Paleozoic strata in this area are relatively flat, and the structural fluctuation per 1 km of plane distance is generally <20 m. The Zijinshan Pluton (diapir magmatic rocks) is located in the southeastern region of the study area (Figure 1).…”
Section: Geological Backgroundmentioning
confidence: 94%
See 2 more Smart Citations
“…The location of the study area is in the L block in the eastern Ordos Basin (Figure 1). It is in the intersection part of the Jinxi Flexural Zone and the Yishan Slope 1,27 . The Upper Paleozoic strata in this area are relatively flat, and the structural fluctuation per 1 km of plane distance is generally <20 m. The Zijinshan Pluton (diapir magmatic rocks) is located in the southeastern region of the study area (Figure 1).…”
Section: Geological Backgroundmentioning
confidence: 94%
“…[20][21][22][23][24][25] The fracture evaluation technology of tight reservoirs is based on the following three aspects: reservoir geological characteristics, rock physics, and geostress properties. [26][27][28] The accurate identification of fractures can help people to better understand the contribution of fractures to fluid seepage, the evolution of fractures and its main controlling factors. 29,30 Logging data have high vertical resolution, so it can be used to identify fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies demonstrate that band structures can be tuned effectively and conveniently according to such a strategy. In our further investigation, a phenomenon is found that the thermal-sensitive materials can own a notable viscoelasticity, which means the storage modulus of materials is strongly dependent on the frequency of wave propagation [27][28][29][30][31]. Previous research shows that the band structures of PCs are considerably influenced by frequencydependent storage modulus.…”
Section: Introductionmentioning
confidence: 95%
“…Surfactants [ 8 , 9 ], polymers [ 10 , 11 ], alkalis [ 12 , 13 ], ions [ 14 , 15 ], foams [ 16 , 17 ], and nanofluids [ 18 , 19 , 20 , 21 , 22 ] and other chemicals were used during the C-EOR process. The mechanism of EOR process was wettability alteration [ 23 , 24 ], interfacial tension decrease [ 25 , 26 , 27 ], structural disjoining pressure alteration [ 28 , 29 ], viscosity decrease [ 30 ], and other mechanisms [ 21 ]. Among these mechanisms, the oil–solid interaction force was the main mechanism of oil recovery.…”
Section: Introductionmentioning
confidence: 99%